Discussion of “How Does Intrinsic Motivation Improve Auditor Judgment in Complex Audit Tasks?” - Vanstraelen, Ann (Contemporary Accounting Research, 2019)
ABSTRACT Kadous and Zhou (2018) investigate experimentally how intrinsic motivation improves auditor judgment in complex audit tasks. In my discussion, I elaborate on my comments from the 2016 CAR Conference. Specifically, I comment in the first part of my discussion on the motivation and contribution of the paper, the underlying theory, the experiment and the results. The second part of my discussion is focused on the broader picture of the paper for which I offer some thoughts based on cross‐fertilization of insights from the archival auditing research and I conclude with providing some suggestions for further research.